Response of a new rumen-derived Bacillus licheniformis to different carbon sources - Cheng, Yuchen; Zhang, Jie; Ren, Wenyi; Zhang, Lili; Xu, Xiaofeng (Frontiers in Microbiology, 2023)
Bacillus Licheniformis (B. Licheniformis) is a microorganism with a wide range of probiotic properties and applications. Isolation and identification of novel strains is a major aspect of microbial research. Besides, the role of different carbon sources affects B. Licheniformis in regulating micro-environment and the mechanisms need to be further investigated. In this study, we first isolated and identified a new strain of B. Licheniformis from bovine rumen fluid, which named B. Licheniformis NXU98. Microcrystalline cellulose (MC) and cellobiose (CB) as two distinct carbon sources to treat strain. Further, a combination of transcriptome and proteome analyses was used to different carbon sources effects. The results showed that B. Licheniformis NXU98 ABC transporter proteins, antibiotic synthesis, flagellar assembly, cellulase-related pathways and proteins were significantly up-regulated in the MC treatment compared to the CB treatment, and lactate metabolism was inhibited. In addition, MC was used as a distinct carbon source to enhance antibacterial ability of B. Licheniformis NXU98, its own disease resistance and to regulate the rumen micro-environment. In conclusion, our research provides a potential new probiotic for feed research and a theoretical basis for investigating the mechanisms by which bacteria respond to different carbon sources.